PENGARUH BERMAIN PASIR KINETIK TERHADAP KREATIVITAS ANAK - Anisah Khamaliyah; Atin Fatimah; Ratih Kusumawardani (Jurnal Penelitian dan Pengembangan Pendidikan Anak Usia Dini, 2019)
Creativity is a mental process of children who are able to produce new works that come from ideas, combinations of data and new information from the surrronding environment. This study aims to determine the effect of kinetic sand play on the creativity of children aged 5-6 years. The study was conducted in the B group of PAUD Rajawali District Tangerang-Banten. The method used in this study is experimental research with a village nonequivalent control group design with a sample of 14 children. Group B1 with a sample of 7 children as the eksperimental class and group B2 with a sample of 7 children as the control class. The instruments used in this study were observation guidelines with data analysis using the SPSS Statistics 22 program. The results showed that the average creativity ability of the control class children at the pretest was 40.00, the experimental class the pretest was 44.27 and the difference in average children’s creativity ability at posttest in the control class is 1.43% and the difference in average children’s creativity ability at posttest in the experimental class is 2.86%. Based on the results of the data obtained, it can be concluded that there is an effect of kinetic sand playing on the creativity of children aged 5-6 years in PAUD Rajawali Tangerang-Banten.